Dating Biblical Jerusalem (The Biblical archaeology review, 2024)
Using radiocarbon dating techniques on more than a hundred organic samples from four different excavation sites in the City of David, scientists have developed a comprehensive "absolute chronology" for Jerusalem from about 1200 BCE until its destruction by the Babylonians in 586 BCE. Their research illuminates many longstanding questions experts have asked about the ancient […]